Anxiety in Patients With Acute Ischemic Stroke: Risk Factors and Effects on Functional Status - Li, Wei; Xiao, Wei-Min; Chen, Yang-Kun; Qu, Jian-Feng; Liu, Yong-Lin; Fang, Xue-Wen; Weng, Han-Yu; Luo, Gen-Pei (Frontiers in Psychiatry, 2019)
Background: Anxiety is prevalent after a stroke. The pathophysiological mechanisms underlying the development of poststroke anxiety (PSA) remain unclear. The aim of this study was to investigate the clinical and neuroimaging risk factors for development of PSA and examine the effects of PSA on activities of daily living (ADL) and quality of life (QOL) in Chinese patients with ischemic stroke. Methods: Two hundred and nineteen patients with acute ischemic stroke were recruited to the study. A series of comprehensive assessments, including Hamilton Anxiety Rating Scale (HARS), Hamilton Depression Rating Scale (HDRS), Lawton ADL scale, and the Stroke-Specific Quality of Life Scale (SSQOL), were conducted in the acute stage and three months after stroke. Magnetic resonance imaging assessment focused on evaluation of infarctions, white matter lesions, and brain atrophy. Results: In the acute stage and 3 months after stroke, 34 (16%) and 33 (15%) patients had PSA, respectively. Multiple logistic regression analysis indicated HDRS (OR=1.269, 95% C.I.=1.182-1.364, P<0.001) and acute infarcts in cerebral hemispheric white matter (CHWM) (OR=2.902, 95% C.I.=1.052-8.007, P=0.040) were significant correlates of PSA in the acute stage of stroke. Three months after stroke, these correlates remained significant predictors, along with male sex.Multiple linear regressions showed that age, NIHSS, HARS and HDRS in the acute stage were significant predictors for both ADL and SSQOL at 3 months after stroke. Conclusion: Depressive symptoms are the major correlates of PSA while more severe PSA is associated with poorer ADL and health-related QOL. Acute lesions involving CHWM may correlate with PSA with mild-to-moderate neurologic deficits, supporting a lesion-location hypothesis in PSA.